Kreativitas Guru Dalam Proses Pembelajaran Bahasa Indonesia Di SMAN 1 Sinjai Borong Kabupaten Sinjai - Akbar Avicenna (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research aims to describe: 1) forms of teacher creativity in the Indonesian language learning process, and 2) inhibiting and supporting factors in efforts to increase teacher creativity at SMA Negeri 1 Sinjai Borong, Sinjai Regency. This type of research is descriptive qualitative. Data collection techniques include: observation, interviews, and documentation. Data analysis techniques by: data reduction, data presentation and verification. The research results found were that teacher creativity in the Indonesian language learning process was generally able to make learning plans, carry out learning using various methods, and carry out assessments appropriately. Inhibiting factors (limited time allocation, lack of supporting facilities and infrastructure, lack of student awareness of the importance of Indonesian language material, and lack of teacher awareness in understanding the meaning and creative learning models in the classroom learning process). Supporting factors (teacher's ability to optimize facilities and infrastructure well, and cooperation between teachers is quite good). Efforts made by teachers to increase creativity (using assignment methods, understanding the importance of creative teachers, carrying out internal training, and activating MGMP forums. It is hoped that the implications of the results of this research can become reference material for the development of further learning strategies (development of designs, methods and class design), so that it is not focused on one learning model, but is varied, and does not bore students in class.